POTENSI BATU KAPUR NUSA PENIDA SEBAGAI AGREGAT PERKERASAN JALAN - Widana Negara, I Nyoman; Suwarsa Putra, Tjokorde Gede (Jurnal Ilmiah Teknik Sipil, 2012)
Nusa Penida Island-Klungkung besides has beautiful views as tourist destination, it also has a potential materials for building and pavement constructions from the large scale of rock lime stone that spreading out on its area. The main objective of the research is to find out the physical characteristic of aggregate and its qualities if it meets the Bina Marga Standard. The sample of rock lime stones were crushed on Aggregate Crushing plan at PT. Sumber Alam Karisma Jaya. The method of descriptive comparative analysis was applied. The sieve analysis results show that both medium and fine grading coarses fulfill the standard requirement of Bina Marga, although the coarse aggregate tends to coarsest. The physical characteristics of Nusa Penida Lime stone namely the bulk density was between 2.4 – 2.5 gr/cm3 and the specific gravity was between 2.54 – 2.6 gr/cm3, in the range of Bina Marga Standard. The absorption was in the range between 1.77 % and 2.7 % which is less than the standard of 3%. The abrasion result was of 27 % that is better than Bina Marga Standard of 40%. It is clearly seen that the Nusa Penida rock lime stone can be used as construction and pavement materials.
Keywords: limestone, road pavement material, Nusa Penida